Peran Alumni Prodi BKI IAIN Syaikh Abdurrahman Siddik Dalam Masyarakat Tahun 2018-2020 - Bohhori, Bohhori; Harista, Eva; Apriyadi, Abi (Department of Islamic Guidance and Counseling, 2023)
Abstract It is hoped that the BKI IAIN SAS Babel Study Program will become a study program that integrates religious knowledge and applicable and strategic da'wah activities to meet the service needs of the people. As well as, it becomes a skills sector to develop the needs of the people of Bangka Belitung. So the reality of alumni in Babel needs to be known. The research method uses qualitative research with data collection techniques through direct and indirect interviews using Google Form media, observation and documentation. The results of the research show that, religious instructors, guidance and counseling teachers, subject teachers, school principals, caregivers of students at Islamic boarding schools, Regional Representative Body (BPD), youth leaders, village government staff. KEYWORDS: Role 1, Alumni 2, BKI Study Program 3, Abstrak Program Studi BKI IAIN SAS Babel diharapkan akan menjadi prodi yang mengintegrasikan ilmu agama dan aktivitas dakwah yang aplikatif dan strategis untuk memenuhi layanan kebutuhan umat. Serta, menjadi bidang keterampilan untuk mengembangkan kebutuhan masyarakat Bangka Belitung. Sehingga realitas alumni di babel perlu untuk di ketahui. Metode penelitian menggunakan penelitian kualitatif dengan Teknik pengumpulan data melalui wawancara secara langsung dan tidak langsung dengan media google form, observasi dan dokumentasi. Adapun hasil penelitian menunjukan bahwa, Penyuluh Agama, Guru BK, Guru mata pelajaran, kepala sekolah, Pengasuh santri di pindok peantren, Badan Perwakilan Daerah (BPD), tokoh pemuda, staf pemerintahan desa. KATA KUNCI: Peran 1, Alumni 2, Prodi BKI 3